On Vocabulary Learning Strategies among Students of Foreign Languages - Slađana D. Stanojević; Ana V. Petrović (University of Belgrade, Teacher Education Faculty, 2020)
Adequate and purposeful use of vocabulary is one of the primary goals of the process of learning and teaching a foreign language, given that the success in building language competence largely depends on it. Vocabulary learning strategies, as a diverse set of techniques focused on overcoming the various problems that arise when learning words, can help students to achieve this complex goal in the easiest and fastest way possible. While some strategies can be applied spontaneously, teaching practice and research (Oxford, 1990; Gu and Johnson, 1996; Schmitt, 1997; Fan, 2003; Šikmanović, 2013) indicate that students are often unaware of the breadth of the range of strategies at their disposal. The main goal of the research presented in this paper is to provide an insight into the attitudes of students of foreign languages towards the use of vocabulary learning strategies, as well as to examine the interrelationships between their attitudes and the perceived use of the strategies. The research was conducted by using a questionnaire on a sample of 47 respondents, and the results showed a significantly developed awareness of students about the usefulness of vocabulary learning strategies, which does not fully correspond to the recorded patterns of using the strategies. It was observed that students use social strategies the least, while they most often use determination and memorisation strategies, but they consider the cognitive and metacognitive types of strategies to be the most useful.